If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -4) = x(x) + -20 Reorder the terms: x(-4 + x) = x(x) + -20 (-4 * x + x * x) = x(x) + -20 (-4x + x2) = x(x) + -20 Multiply x * x -4x + x2 = x2 + -20 Reorder the terms: -4x + x2 = -20 + x2 Add '-1x2' to each side of the equation. -4x + x2 + -1x2 = -20 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -4x + 0 = -20 + x2 + -1x2 -4x = -20 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -4x = -20 + 0 -4x = -20 Solving -4x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-4'. x = 5 Simplifying x = 5
| 4/5x^2=0 | | x+3+x+x-6=30 | | -5x+24y=200 | | 7-x+4=y | | 9+x-y+3=14 | | x^2-8xy+15y^2+2x-10y=0 | | x=22+6 | | 24+x=55 | | 14-x-8-x=0 | | X+4-3=31 | | X+3*y=15.6 | | 4/√p^3=4p | | X+3*y=31 | | X+3xy=31 | | p^2+7p=q^2+7q | | X/7x4=19 | | 4/√p^3 | | tan^3(x-(1/343) | | 5+x+6+2x+5+x^2+8= | | y=(3x-7)(6x^2-7x) | | 24+3x+x^2=6 | | 24+3x+x^2= | | y^2-40y-3=0 | | 4p^3/2=4p | | 3z-8=4 | | 5t+8=8 | | 18k-3=6 | | 3x+(x+4/3)=(5x+6/2) | | (x^2-x-5)(2x+3)= | | (x^2-x-5)(2x+3)=0 | | 5x+3(5x-2)=14 | | 6(3x+2)-5(6x-1)=3(x-8)-5(7x-6)+9 |